การศึกษาความต้องการการพยาบาลของผู้ป่วยอายุรกรรมที่จำหน่ายจากโรงพยาบาลศูนย์ สังกัดกระทรวงสาธารณสุข - วิรงรอง ชมภูมิ่ง (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this research were to study the nursing care needs of the discharged medical’s patients in medical centers, Ministry of Public Health. Participants were 401 discharged medical’s patients, which were discharged in hospital, and were selected by multi-stage random sampling. Research instrument were Nursing Care Needs which were tested for content validity and reliability. The reliabilities were .83, .84 and .86 respectively. Data were analyzed including frequency, mean, standard deviation, t-test and One way ANOVA. Finding were as follows;1.The nursing care needs of the medical’s patients was at the medium level (X = 2.17), nursing‘s information needs, psychological/spiritual needs and physical needs was at the medium level (X = 2.29, X = 2.17 and X = 1.99 respectively).2.Sex, age, education, family income, illness experience and illness’s type were not significant with the nursing care needs.The different of medical patients condition such as activity daily living (ADL) significant value at .05